Case study report of IKEA Damansara / Adlan Khairulfazi … [et al.] - KHAIRULFAZI, ADLAN; AHMAD MALIKI, SITI NUR SAKINAH; MOHD ZAIN, NUR ZULAIKHA; NASIR, FAEZU (2019)
IKEA is a Swedish founded, Dutch based multifunctional: group, that designs and sells ready- to-assemble furniture,, kitchen; appliances and home accessories. It is one of Malaysia's largest furniture retailer. And now, it has ventured in the food industry. Serving mains to desserts, it now features, restaurant, cafe and bistro. Customers can pop: in for a quick snack or stay for a leisurely breakfast, lunch or dinner. IKEA stores feature restaurants, bistros and one of the most popular food item is the vanillas oft ice cream. People are willing to wait in a long queue just to obtain the ice cream. However, observation and experience: show that the buying: and; selling: process of IKEA's vanilla soft ice cream is a troublesome; to both; the customers and staff members, of IKEA. Thus, the team would like to analyse the issue, long; queue of purchasing and selling vanila soft ice cream in IKEA Damansara.